RESPON PEMBERIAN PUPUK KANDANG KAMBING DAN PUPUK KANDANG AYAM TERHADAP PERTUMBUHAN DAN HASIL TANAMAN PAKCOY (Brassica rapa L.) - Vera Veronika; I Gusti Ayu Diah Yuniti; Komang Dean Ananda; Made Sukerta; Farida Hanum (Agrofarm: Jurnal Agroteknologi, 2023)
Pakcoy (Brassica rapa L.} is one of the leaf vegetables that has very easy cultivation techniques to develop, the pakcoy plant is very potential and has good prospects. Sources of essential vitamins and minerals that contain lots of fiber are needed by humans. The purpose of this research is The purpose of this study was to determine the growth response and yield of pakcoy (Brassica rapa L.) due to the application of goat manure and chicken manure and to determine the best dose interaction of goat manure and chicken manure on increasing the growth and yield of pakcoy (Brassica rapa L) as a result of giving goat manure and chicken manure and knowing the best dose interaction of goat manure and chicken manure on increasing growth and yield of pakcoy (Brassica rapa L). This study used a Randomized Block Design (RAK) consisting of 25 combination treatments and repeated 3 (three) times so that 75 experimental pots were obtained. Each polybag pot contains 5 kg of soil. The results showed that giving a dose of 50 g / 5 kg of goat manure soil and a dose of 50 g / 5 kg of chicken manure gave a very significant effect on the observed parameters, namely: plant height (g), number of leaves (strands), weight total plant fresh (g) and total plant dry weight (g).